Recommendations for advancing mixoplankton research through empirical-model integration - Millette, Nicole C.; Leles, Suzana G.; Johnson, Matthew D.; Maloney, Ashley E.; Brownlee, Emily F.; Cohen, Natalie R.; Duhamel, Solange; Poulton, Nicole J.; Princiotta, Sarah D.; Stamieszkin, Karen; Wilken, Susanne; Moeller, Holly V. (Frontiers in Marine Science, 2024)
Protist plankton can be divided into three main groups: phytoplankton, zooplankton, and mixoplankton. In situ methods for studying phytoplankton and zooplankton are relatively straightforward since they generally target chlorophyll/photosynthesis or grazing activity, while the integration of both processes within a single cell makes mixoplankton inherently challenging to study. As a result, we understand less about mixoplankton physiology and their role in food webs, biogeochemical cycling, and ecosystems compared to phytoplankton and zooplankton. In this paper, we posit that by merging conventional techniques, such as microscopy and physiological data, with innovative methods like in situ single-cell sorting and omics datasets, in conjunction with a diverse array of modeling approaches ranging from single-cell modeling to comprehensive Earth system models, we can propel mixoplankton research into the forefront of aquatic ecology. We present eight crucial research questions pertaining to mixoplankton and mixotrophy, and briefly outline a combination of existing methods and models that can be used to address each question. Our intent is to encourage more interdisciplinary research on mixoplankton, thereby expanding the scope of data acquisition and knowledge accumulation for this understudied yet critical component of aquatic ecosystems.